Implementasi dan Dampak Penggunaan Sistem Rekam Medis Elektronik (RME) pada Pelayanan Kesehatan - Yuana Wangsa Putri; Tini Rezeki Saragih; Sri Hajijah Purba (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
The implementation of electronic medical records (EMR) in the health sector is one of the technological innovations that has the potential to improve the quality of health services. EMR implementation can improve documentation accuracy, accelerate access to patient data, and support the efficiency of medical personnel. The purpose of this study is to determine the impact of EMR implementation on healthcare services including the challenges faced during its implementation. The research methodology will use a systematic literature review by analyzing papers from the last five years. The results show that RME plays an important role in improving healthcare quality, patient satisfaction, reducing medical errors, and improving coordination between healthcare professionals. However, the implementation of RME is not without obstacles, such as limited technological infrastructure, lack of training of health workers, resistance to change, and patient data security issues. Optimizing its implementation requires government policy support, regular training for health workers, and improved IT infrastructure. In conclusion, despite the challenges, with the support of various stakeholders, RME can have a significant positive impact on the quality of healthcare services in Indonesia. It is hoped that this study can provide insights for policy makers and healthcare providers to maximize the implementation of RME in a sustainable manner.